About forming of personality physical culture of students in the process of physical education (in aspect of presence of abilities) - S.I. Belykh; S.A. Chernigovskaia (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
It is shown that practice of teaching of discipline «Physical education» does not provide forming of volume of abilities, sufficient for the origin of athletic activity. Prevail ability to pick up a place, sporting form, inventory depending on the type of physical exercises and ability on the observance of rules of the personal hygiene. In the questionnaire questioning 650 students (324 youths and 326 girls of the first and fourth courses) took part. All of students visited employments on physical education at school and institute of higher. It is marked that the important task of amateurish athletic education is forming for the students of the personal experience of independent athletic, health and рекреационных employments. It is underlined that sense of amateurish athletic education of students consists in achievement by a man unity of mental and activity processes. Such processes are needed for an estimation and understanding of the state of the health, programming and residence of healthy way of life.